Staggered completion of the European Banking Union: Transposition dates of the BRRD. Data record description - Michael Koetter; Thomas Krause; Eleonora Sfrappini; Lena Tonzer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2021)
In May 2014, the European Commission published the Bank Recovery and Resolution Directive (BRRD). The directive introduces rules on bank resolution and restructuring including a bailin tool. It constitutes the legal foundation underlying the Single Resolution Mechanism (SRM). Member countries of the European Union (EU) had to transpose this directive into national law by 31 December 2014 and implement the rules on resolution and restructuring of failing banks from 1 January 2015 onwards. However, many countries delayed the implementation. We assemble a dataset on national transposition dates of the BRRD across the EU-27 countries.
urn:nbn:de:gbv:3:2-135805
Keywords: 330